World Heritage: Where Are We? An Empirical Analysis - Bruno S. Frey; Paolo Pamini (Center for Research in Economics, Management and the Arts (CREMA), 2011)
A statistical analysis of the UNESCO World Heritage List is presented. The World Heritage Convention intends to protect global heritage of outstanding value to mankind, but there has been great concern about the missing representativity of the member countries. There is a strongly biased distribution of Sites according to a country's population, area or per capita income. The paper reveals the facts but refrains from judging whether the existing distribution is appropriate or not. This task must be left to the discussion in the World Heritage Convention.
Keywords: Z11; F5; H87; 330; global public goods; world heritage; international organizations; international political economy; culture; UNESCO